2021
DOI: 10.1111/jcpe.13474
|View full text |Cite
|
Sign up to set email alerts
|

A tissue‐engineered biocomplex for periodontal reconstruction. A proof‐of‐principle randomized clinical study

Abstract: Aim: To assess the safety/efficacy of a tissue-engineered biocomplex in periodontal reconstruction.Methods: Twenty-seven intrabony defects were block-randomized across three treatment groups: Group-A (N A = 9) received autologous clinical-grade alveolar bone marrow mesenchymal stem cells (a-BMMSCs), seeded into collagen scaffolds, enriched with autologous fibrin/platelet lysate (aFPL). In Group-B (N B = 10), the collagen scaffold/aFPL devoid of a-BMMSCs filled the osseous defect. Group-C (N C = 8) received Min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 62 publications
0
40
0
Order By: Relevance
“…Recently, clinical studies on periodontal tissue regeneration by stem cell transplantation in humans have been reported. In three of these studies, there was a trend toward improvement of clinical parameters in the stem cell transplantation group; however, no statistically significant differences were observed [60,62,63]. Autologous cells were used in these studies, and the results of the studies differed from the results of previous animal studies.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Recently, clinical studies on periodontal tissue regeneration by stem cell transplantation in humans have been reported. In three of these studies, there was a trend toward improvement of clinical parameters in the stem cell transplantation group; however, no statistically significant differences were observed [60,62,63]. Autologous cells were used in these studies, and the results of the studies differed from the results of previous animal studies.…”
Section: Discussionmentioning
confidence: 91%
“…Human clinical studies have already begun based on these animal studies. The results of the controlled clinical trial in human patients are summarized in Table 2 [59][60][61][62][63]. All of these studies confirmed the safety of stem cell transplantation and reported that clinical parameters such as pocket depth, clinical attachment level, and radiographic bone volume tended to improve by stem cell transplantation [59][60][61][62][63].…”
Section: Periodontal Regeneration By Stem Cell Transplantationmentioning
confidence: 98%
See 2 more Smart Citations
“…Culture-expanded MSCs have been successfully used in regenerative medicine in combination with biomaterials for the regeneration of oral and maxillofacial bone deficiencies [45][46][47][48]. Despite these promising clinical results, the use of autologous MSCs has some major limitations such as regulatory constraints, costs for amplification and quality controls, logistics of transportation, and surgical appliance of fresh cells and patient-to-patient variability in the cell expansion efficiency and regenerative outcome [49][50][51].…”
Section: Regenerative Potential Of Mesenchymal Stem Cellsmentioning
confidence: 99%